Speaking clock / Noor Hawa Hasran and Rahidah Mahma - Hasran, Noor Hawa; Mahma, Rahidah (1989)
This speaking clock project is formed by a simple microprocessor controller system. The system is used to process data from the real time clock. A computer is a device to process data automatically. Processing consists of storing data in memory, performing logical operation and taking decisions based on a data. Some computer are used to operate such devices as video recorder or irl ocks., Most of the actual work is done by the central processing unit (CPU). The CPU consists of a single integrated circuit; a microprocessor. This is driven by an astable circuit. This project describes how the allophone speech system can be used to produced a speaking clock which may be invaluable to a blind person or simply a novelty clock demonstrating the use of current electronic devices. The majority of the SP0256AL speech synthesiserhave been used with this project.